Population density of nematodes associated to maize cultivation (Zea plus L.) in the regions of Puno and Cusco - Lima-Medina, Israel Israel (2017)
Corn (Zea mays L.) is a cereal of global importance for its different industrial uses and nutritive value. Like other crops, it is affected by pests, including nematodes, whose presence in the maize crop causes a decrease in yields, so the present work is presented. In order to determine the population density of nematodes associated with maize cultivation in the regions of Puno and Cusco; For which 121 soil samples were collected during the 2015-2016 campaign in the Puno Region, in the districts of Chupa, Sandia, San Juan del Oro, Cuyocuyo, Ayapata, Ollachea and San Gabán; And 30 samples from the Cusco Region, in the districts of Pisac and Urubamba. Were identified the genera genera Helicotylenchus spp. and verified. (32-100%), Mesocriconema spp. (33.3-63.8%), Globodera spp. (96-100%), Xiphinema spp. (11-36.6%), Rotylenchus spp. (20-77.2%) and Dorylaimus spp. (7.7%). It was also observed the presence of free-living nematodes (Saprophytes and predators) (96-100%). The most prevalent nematodes in all areas were Helicotylenchus, Mesocriconema and free-living nematodes.